2012
DOI: 10.3402/tellusb.v64i0.17735
|View full text |Cite
|
Sign up to set email alerts
|

Iron content and solubility in dust from high-alpine snow along a north-south transect of High Asia

Abstract: A B S T R A C T This study describes the dissolved and insoluble iron fraction of dust (mineral aerosol) in high-alpine snow samples collected along a north-south transect across High Asia (Eastern Tien Shan, Qilian Shan, and Southern Tibetan Plateau). This dust provides the basic chemical properties of mid-and high-level tropospheric Asian dust that can supply the limiting iron nutrient for phytoplankton growth in the North Pacific. The iron content in Asian dust averages 4.95% in Eastern Tien Shan, 3.38Á5.41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(60 reference statements)
2
8
0
Order By: Relevance
“…4). Our data were similar to the previous reported iron contents in dust particles preserved in ice cores across the TP (Wu et al, 2012), which ranged from 3.38 % to 5.41 %. The iron in the cryoconite on the TP glaciers represents a natural background level.…”
Section: Abundance Of Elemental Fe (Total) and Free Fe (Iron Oxides)supporting
confidence: 92%
See 1 more Smart Citation
“…4). Our data were similar to the previous reported iron contents in dust particles preserved in ice cores across the TP (Wu et al, 2012), which ranged from 3.38 % to 5.41 %. The iron in the cryoconite on the TP glaciers represents a natural background level.…”
Section: Abundance Of Elemental Fe (Total) and Free Fe (Iron Oxides)supporting
confidence: 92%
“…Compared to dust and BC, the composition and sources of organic matter over the glacier surface are complicated. Organic matter was a mixture of soil humic and humic-like matter, biogenic particles (e.g., algae, fungi and plant debris), and biomass/fossil fuel burning emissions (Wu et al, 2016), which are often termed brown carbon (BrC). Considering its diverse sources and complex composition, in this work we did not assume the specific optical parameters for organic matter.…”
Section: Contribution To Light Absorption By Cryoconite Componentsmentioning
confidence: 99%
“…Our data were similar to the previous reported iron contents in dust particles preserved in ice cores across Tibetan Plateau (Wu et al, 2012), which ranged from 3.38% to 5.41%. The iron in the cryoconite on the TP glaciers represents a natural background level.…”
Section: Abundance Of Elemental Fe (Total) and Free-fe (Iron Oxides)supporting
confidence: 92%
“…A previous study has revealed that the abundance of iron in ice core dust differs along the north-south transect of High Asia (Wu et al, 2012). In this study, new data from four ice cores in the central and western Tibetan Plateau are presented ( Table 1).…”
Section: Iron Abundance In Ice Core Dustmentioning
confidence: 90%